INSECURITY AND TERRORISTS’ THREATS OF ATTACKS ON SELECTED NIGERIAN CITIES: IMPLICATIONS ON LAGOS RESIDENTS’ CONCERNS FOR SAFETY AND THE CITY SECURITY PLANNING - Badiora, Adewumi Israel; Aborisade, Richard Abayomi (UCC Law Journal, 2024)
Terrorism is common but limited to certain towns in Nigeria. However, the nomenclature seems to be changing as security intelligence has it that terrorist groups are planning attacks targeting Lagos, and other notable cities. This study therefore examines concerns for safety among residents and implications on individual and city-level security planning in Lagos. The official wards as demarcated by the Independent National Electoral Commission represent clusters from which at least a respondent was randomly selected. The study’s respondents were selected from 49 (one of every five wards 20%) wards out of 245 wards in Lagos. In the selected wards, at least two respondents were randomly selected. A total of 288 residents participated in the survey, but, only 134 respondents accurately completed the questionnaire used in this analysis, representing a 58.7% response rate. Results show that 78% of the respondents were concerned about their safety while some 90% took precaution by avoiding certain places and activities. Findings show significant relations between awareness of the planned attacks, concerns for safety, and precautionary behaviour among respondents. Besides, results show that respondents’ socio-economic characteristics, neighbourhood environmental design, and past crime victimisation mediate concerns for safety and security behaviour. The study concludes that the emergence of this security intelligence in the public domain has further contributed to the increasing fear and residents’ mobility change. The study recommends among others policing strategies, a new urbanism, where urban planning and design strategies are applied to make attacks more difficult to carry out in soft spaces and places.